Eksistensi Kerajinan Keramik Terhadap Minat Generasi Muda Di Tengah Maraknya Pabrik Garmen Di Kecamatan Mayong Jepara - Yusuf, Muhammad Syaifullah; Arsal, Thriwaty (Faculty of Social Science, Universitas Negeri Padang, 2025)
Mayong Lor has been known as a center of the ceramic industry for centuries and has been passed down from generation to generation. With the changing times, the condition of Mayong Lor ceramics is now facing serious challenges, namely a regeneration crisis. The younger generation is showing decreasing interest in the ceramic craft profession. Furthermore, the rapidly expanding number of factories in Jepara has led the younger generation to choose to work in factories. The purpose of this study is to determine the interest of the younger generation in the existence of ceramic crafts amidst the rise of garment factories.This study uses a qualitative research method with a descriptive analysis approach. Data collection uses a snowball sampling technique, data sources are obtained through observation, interviews, and documentation. The results of this study indicate that ceramic crafts are increasingly declining, the majority of craftsmen are currently elderly and many have died. The main factor causing the change in interest of the younger generation towards ceramic crafts is the consideration of income obtained because the younger generation thinks that working in a factory is more certain and more quickly profitable. In addition, ceramic crafts are also considered old-fashioned and outdated, the process of making ceramics is difficult, heavy, and dirty because it is related to soil. This change in interest of the younger generation has caused the ceramic crafts in Mayong Lor Village to decline.